OXYGEN REACTIVE SUBSTANCES (ROS) IN FROZEN-THAWED SEMEN IN PIG - Vasco Mora, Diana (2008)
The ROS generation was measured by flow citometry in thawed sperm samples incubated without (basal levels) or with (induced levels) a ROS inductor (1 mM tert-butyl hydroperoxide) for 30 min at 39 ºC and 5% CO2. Sperm cells were simultaneously stained with 2’, 7’-dichlorodihydrofluorescein diacetate, acetil ester (1 mM, CM-H2DCFDA), to estimate the production of ROS, and propidium iodide (1.5 mM) to exclude dead sperm from the analysis. The ejaculates from nine boars were frozen with 3% of glycerol and warmed at ~1200 or ~1800ºC min-1. The ROS production was measured at 0, 60, 120, 240 y 360 min in sperm samples hold at ~21-23 ºC (not incubated) or at 39 ºC and 5% CO2 (incubated) over time. Warming rate had not influence (P>0.05) on ROS production. ROS generation was constant (P>0.05) over time in not incubated samples, but it showed a progressive increase in incubated samples, being it significant (P<0.05) from the 120 min in basal levels or 60 min of incubation in induced levels. Significant (P>0.01) ejaculate/boar variability was evident in both basal and induced ROS production in the incubated sperm samples. Both basal and induced ROS production were significantly (P<0.01) correlated with the percentages of total and rapid progressive, motile and viable spermatozoa. The technique is of great utility to evaluate functional capacity in frozen-thawed sperms; however, additional studies are required to standardize the same one and to establish indicative thresholds of sperm quality loss.